Numerical investigation of tunnelling effects on existing piles in structured clay. Issue 16 (10th December 2022) - Liu, Jun-Xiu; Yang, Jie; Liu, Ying-Jing; Zhu, Shu; Laouafa, Farid
Abstract: Tunnel construction may induce ground deformations and affect the adjacent pile foundations. Up to now, few studies have investigated the soil-tunnel-pile interaction in structured clay. In this study, an anisotropic structured clay model is implemented in the finite-difference code FLAC 3D to investigate the effects of tunnelling on existing piles in structured clay. The model is first calibrated based on the oedometer and undrained triaxial tests for Shanghai structured clay. Then the numerical model and the modelling procedure are introduced and validated by simulating the centrifuge model tests of tunnelling adjacent to piles in remoulded kaolin clay. Thereafter, influences of clay anisotropy and structure on the existing piles due to tunnelling are investigated using the calibrated parameters for Shanghai structured clay. It is observed that the influence of clay structure on the shape of the deflection and bending moment of the pile is not significant. However, the introduction of the anisotropy and the adhesive mean stress may reduce the ground settlement while increasing the lateral soil movement at the tunnel axis depth, whereas the introduction of the bonding ratio may have the opposite effect. Moreover, introducing both the anisotropy and the soil structure will lead to the increase of pile moment.